Causation in a timeless world? - Tallant, Jonathan (Taylor and Francis, 2018)
This paper is an attempt to answer the question, 'could there be causation in a timeless world?' My conclusion: tentatively, yes. The paper and argument have three parts. Part one introduces salient issues and spells out the importance of this (initially somewhat baroque seeming) line of investigation. Section two of the paper reviews recent arguments due to Baron and Miller (2015a), who argue in favor of the possibility of causation in a timeless world, and looks to reject their arguments developed there. Section three is a response to a response. In their (2015a), Baron and Miller also argue that an argument in favor of the possibility of causation at timeless worlds, that I put forward (Tallant, 2008), is an argument that fails. In section three, my response to Baron and Miller is that their argument against me succeeds, but that there is a nearby argument that we can appeal to in order to demonstrate the possibility of causation at timeless worlds.